Fungsi bahasa dan makna pragmatik dalam media sosial untuk memerangi Covid-19: Kajian etnopragmatik - Pranowo Pranowo; Diani Febriasari (BAHASTRA, 2020)
This article discusses the function of language and pragmatic meaning in social media to combat Covid-19. Theoretical references used are ethnopragmatics. Ethnographic studies basically examine language from a cultural aspect. Cultural aspects include knowledge, behavior, and artifacts. Meanwhile, pragmatics is a study of language use on the basis of context. This research uses data sources from Instagram, Facebook, WA, and email. Research data in the form of language use in social media above. Data from Instagram and Facebook are downloaded from the internet, while data from email is collected through the direction of researchers with guidance on the instrument. Data collection techniques are done through reading and taking notes. Concrete data analysis techniques are carried out through data identification, data classification, data interpretation, and reporting in the form of journal articles. The findings of research on language subfunctions include asking, inviting or influencing, being sarcastic, motivating and criticizing, and saying thank you. Meanwhile, the pragmatic meaning used in social media includes indirectly advising,Â  persuading, indirectly reminding, subtly insinuating, inviting, complaining, and give advice.